2007
DOI: 10.1128/mcb.00439-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transcription Factor Kar4 in Regulating Downstream Events in the Saccharomyces cerevisiae Pheromone Response Pathway

Abstract: Yeast Kar4 is a putative transcription factor required for karyogamy (the fusion of haploid nuclei during mating) and possibly other functions. Previously known to be required only for the transcriptional induction of KAR3 and CIK1, microarray experiments identified many genes regulated by Kar4 in both mating and mitosis. Several gene clusters are positively or negatively regulated by mating pheromone in a Kar4-dependent manner. Chromatin immunoprecipitation and gel shift assays confirmed that Kar4 binds to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 46 publications
1
56
0
Order By: Relevance
“…and mating projection (GO:0005937, P = 1.37310 À6 ), consistent with Kar4's known function in the pheromone response pathway (Kurihara et al 1996;Lahav et al 2007). Taken together, these results demonstrate that Calling Card-seq can analyze multiple transcription factors in parallel and is accurate, high-throughput, and can be used to discover novel target genes and binding motifs for transcription factors.…”
Section: Calling Card-seq Enables Analysis Of Multiple Tfs In a Singlsupporting
confidence: 72%
See 1 more Smart Citation
“…and mating projection (GO:0005937, P = 1.37310 À6 ), consistent with Kar4's known function in the pheromone response pathway (Kurihara et al 1996;Lahav et al 2007). Taken together, these results demonstrate that Calling Card-seq can analyze multiple transcription factors in parallel and is accurate, high-throughput, and can be used to discover novel target genes and binding motifs for transcription factors.…”
Section: Calling Card-seq Enables Analysis Of Multiple Tfs In a Singlsupporting
confidence: 72%
“…3; Supplemental Tables 3, 4). These results indicate that Kar4 and Rpi1 may bind a PSWM with low information content missed by our search and may require coactivators (Lahav et al 2007), and we were able to identify a weak Ste12 motif upstream of Kar4 target genes. The patterns of Calling Card insertions deposited by Lee1 and Sfg1 are similar to a control strain that lacked a TF-Sir4 fusion, which suggests that, if the Sir4 has not disrupted their DNA-binding specificity, these proteins may not bind to DNA, or may bind to DNA nonspecifically (Supplemental Fig.…”
Section: Calling Card-seq Enables Analysis Of Multiple Tfs In a Singlmentioning
confidence: 54%
“…This is likely due to an interaction of Kar3 with the mating-specific Ga subunit of a trimeric G protein involved in pheromone signaling (Zaichick et al 2009). Pheromone stimulation increases the expression of KAR3 and CIK1 via activation of the transcription factors Ste12 and Kar4 (Kurihara et al 1996;Gammie et al 1999;Lahav et al 2007) and underlies the expression of the shorter NLS-less cytoplasmic Cik1 variant (Manning et al 1999;Benanti et al 2009). Thus, the cytoplasmic localization of Cik1 targets Kar3 to its cytoplasmic binding sites (i.e., the MT plus ends) (Sproul et al 2005) and, as shown in this study, the cytoplasmic side of the SPB through a Cik1-codependent interaction of its N-terminal domain with Spc72.…”
Section: Discussionmentioning
confidence: 99%
“…Other differences between the mating processes in S. cerevisiae and C. albicans may be quantitative rather than qualitative. For example, the transcriptional response to pheromone in C. albicans appears to increase gradually over several hours, while that in S. cerevisiae reaches maximal levels within several minutes of pheromone exposure (1,25,43). The BAR1 gene may play a role in some of the observed differences in pheromone responses between fungal species.…”
Section: Figmentioning
confidence: 99%